FREQUENCY OF SYMPTOMATIC SPONTANEOUS BACTERIAL PERITONITIS AND ASSOCIATED CLINICAL PARAMETERS IN PATIENTS WITH LIVER CIRRHOSIS - Syed Fayyaz Mehmood Gilani (Army Medical College Rawalpindi, 2021)
Objective: To study association between spontaneous bacterial peritonitis and clinical symptoms in liver cirrhosis.